Effect of Number of Passengers [Loading] on Centre of Gravity of a Three Wheeled Vehicle [Keke-Napep] - Sunday, B.; Thomas, U.; Ityokumbul, I. S.; Nasir, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In order to combat insecurity and to reduce the rate of accidents caused by commercial motorcyclist; many States Government in Northern Nigeria have substituted the use of motor cycles commonly known as Okada, with the use of three wheeled vehicle commonly known as keke-napep. The Static and dynamic characteristics of these vehicles are not as those of the usual vehicles. Therefore, the need to know more about the effects loading on these vehicles is highly needed by Nigerians in order to ensure good road and passengers’ safety. This paper uses simple approach to highlight the effects of number of passengers (loading) on the position of Centre of Gravity (CG) of the three wheeled vehicles. It will serve as a measure for ensuring safe riding and reducing road clashes. As the load on the three wheeled vehicle increases from 3505N to 5410N, the Static Stability Factor decreases. This reduces the safety margin against rollover of the three wheeled vehicles compared to those of the four wheeled vehicles. The keke-napep is a rear wheel drive vehicle with rear engine and rear passenger arrangement. It subjects the vehicle to high weight transfer during braking. This causes the change in position of Centre of Gravity and the instability of the three wheeled vehicles. Therefore, it is hereby recommended that the wheelbase, track length, loading space and the Centre of Gravity position should be given a critical consideration during chassis design in order to improve the static and dynamic stability of these vehicles. Also, Components such as the engine and transmission system should be rearranged to obtain a more reliable position of the Centre of Gravity.